Social Resilience and Challenges of Covid-19 - Debele, Efa Tadesse (Technium Business and Management, 2022)
These days the world has been facing ever seen multi-dimensional crisis due to new deadly disease known as Covid-19. Even though world is not stranger for different catastrophic events recently the outbreak of Covid-19 came up with ever seen difficulties which tested the resilience of different societies. Covid-19 came to social world when the globalization era celebrates its hegemonic inevitabilities. So far different pandemic visited human society and none of them were not mysterious compared to Covid-19. Those pandemic were either partly or completely controlled by the then human knowledge and technologies. However, Covid-19 tested hitherto medical knowledge and health system of all societies regardless of their level of advancement. Yet different societies experienced Covid-19 challenges and pains differently. This trend may provoke the question of covid-19 varying factors and the overall nature of a given Society. Covid- 19 deadly affected almost all societies regardless of their technological and medical advancement. So far Covid-19 distracts all elements of social systems such as social life, political life, cultural life, spiritual life, economic life and overall social existence. Different societies used to withstand covid-19 challenges with different affordable and relevant strategies. Different aspects of society have been affected. In this article, it is needed to penetrate into varying intensity secrets complicated the pandemic despite knowledge gap and limitation of medical knowledge in case of exhaustive awareness of etiology of viruses.